An Ethnography Study Of Shared Values Woman As Mining Blast Engineer - Pratama, Renaldo; Enny, Enny; Alex Fernando Hasahatan; Jerry Heikal (CV. ULIL ALBAB CORP, 2025)
This research examines the shared values of women working as mining blast engineers in the mining industry. Through a qualitative approach with a realist ethnographic design, this study analyzes the experiences, perspectives, and adaptation strategies of three female mining blast engineers. The shared values owned by the respondents before entering the blast engineer job are independent character, confidence, courage, toughness, assertiveness, strong faith, respect, professionalism and trustworthiness. Pain values include long work schedules, distant work locations, male-dominated work environments, and fatigue due to work and field conditions. Meanwhile, the shared values formed from these pain values are characters who are brave, tough, assertive, respectful, environmentally sound, professional and trustworthy. These values enable them to adapt, survive and thrive in their field of work. The research also found that the implementation of gender diversity policies has a positive impact on the availability of a safe and conducive working atmosphere and environment. This policy allows all workers, regardless of gender, to have the same duties and responsibilities. It also has an impact on more conducive internal and external work processes, with a focus on work processes and outcomes, rather than on who is working on the project. This research concludes that women have great potential to become mining blast engineers in the mining industry. And the wider implementation of gender diversity policies in mining companies can help create a more inclusive work environment and encourage women's participation in important positions such as mining blast engineer.